Mobile application leads to psychological improvement and correlated neuroimmune function change in subjective cognitive decline - Merav Catalogna; Nira Saporta; Bar Nathansohn-Levi; Tal Tamir; Ariel Shahaf; Shira Molcho; Shai Erlich; Shahar Shelly; Amir Amedi (npj Digital Medicine)
Abstract Subjective cognitive decline (SCD) is a potential early marker of neurodegeneration, with negative affective states such as depression and anxiety significantly contributing to cognitive impairment. Digital treatments show promise, yet evidence of their use and efficacy in SCD remains limited. We studied 103 individuals aged 50-65, experiencing SCD and heightened anxiety, randomly assigned to a three-week mobile app program or waitlist control. Assessments included psychological measures, immunological analysis, and for a subgroup of the participants also resting-state functional connectivity (rsFC). The intervention significantly reduced proinflammatory mediators (TNF-α, IL-17, IL-23, MCP-1, IFN-γ, and IL-12) and improved depression, anxiety, resilience and well-being with sustained effect over a three-week follow-up. RsFC results show enhanced fronto-limbic connectivity correlated with the psychological and immunological changes, with the insula emerging as a key hub mediating these relationships. These findings highlight digital treatments as potential scalable, brain-immune targeted interventions for SCD and other medical conditions.